Identification of Potential Private Green Open Space (GOS) in the Ngantru Urban Area using the Supervised Land Classification Method - Rita Parmawati; Indra Purnama Putra; Deni Agus Setyono; Reni Sri Hapsari; Ahmad Ibnu Riza; Annisa Nurul Hakim (Jurnal Penelitian Pendidikan IPA, 2026)
Population growth and urban activities have caused land conversion and decreased environmental carrying capacity. The existence of Green Open Space (GOS) is crucial in improving environmental quality and increasing community welfare. In Ngantru Urban Area, data collection on private GOS is still incomplete, although this is important to increase the Land Quality Index in Tulungagung Regency. Using the Supervised Land Classification method allows for more accurate identification and mapping of private GOS potential through remote sensing data analysis. Based on the results of the analysis, private GOS in Ngantru Urban Area consists of agricultural land covering an area of 1,694.35 hectares. Padangan Sub-district has the largest area, namely 321.04 hectares or 18.95% of the total area of private GOS, followed by Pojok Sub-district with 287.09 hectares or 16.94%. The difference in the area of private GOS between Sub-districts reflects the diverse development potential in each region. This data is an important basis for formulating more effective and sustainable spatial planning policies, as well as supporting targeted environmental conservation efforts to improve the quality of life of the community.